2021
DOI: 10.20535/2410-8286.226588
|View full text |Cite
|
Sign up to set email alerts
|

Clil in Tourism Students’ Multicultural Competence Development

Abstract: The current study aims at implementation of the Content and Language Integrated Learning (CLIL) as an educational approach in tourism students’ multicultural competence development. To achieve the goal, a mixed-method was chosen, which implied the use of quantitative and qualitative research methods. The quantitative method was used to process the test results of tourism students and determine the statistical significance of the results obtained during the experiment, the qualitative method was used to analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…These learning techniques also had a significant effect on the students' language achievement as these techniques stimulated their communicative interactions. It was also mentioned that various interactive methods and activities enabled the students to practise communicative skills (Goncharova et al, 2021). Moreover, in CLIL implementation, it was suggested that the lecturers did not apply only a single technique to activate the students (Zhyrun, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These learning techniques also had a significant effect on the students' language achievement as these techniques stimulated their communicative interactions. It was also mentioned that various interactive methods and activities enabled the students to practise communicative skills (Goncharova et al, 2021). Moreover, in CLIL implementation, it was suggested that the lecturers did not apply only a single technique to activate the students (Zhyrun, 2016).…”
Section: Discussionmentioning
confidence: 99%